2015
DOI: 10.3109/02699052.2015.1043345
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an attention and memory intervention post-childhood acquired brain injury: Preliminary efficacy, immediate and 6 months post-intervention

Abstract: Preliminary results provide support for the efficacy of the Amat-c post-childhood ABI. A larger study is needed to confirm these findings, as a reduction in attention and memory difficulties will enhance everyday functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 54 publications
(61 reference statements)
0
13
0
1
Order By: Relevance
“…Our search yielded 20 articles discussing 19 studies which in total investigated 17 different cognitive rehabilitation interventions. Seven relevant new studies (33)(34)(35)(36)(37)(38)53) were found which, to the authors' knowledge, have never been included before in reviews on cognitive rehabilitation for children and adolescents with ABI and therefore add important new knowledge to the limited evidence-base presented in previous reviews.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our search yielded 20 articles discussing 19 studies which in total investigated 17 different cognitive rehabilitation interventions. Seven relevant new studies (33)(34)(35)(36)(37)(38)53) were found which, to the authors' knowledge, have never been included before in reviews on cognitive rehabilitation for children and adolescents with ABI and therefore add important new knowledge to the limited evidence-base presented in previous reviews.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the authors decided to exclude these studies from the present review. E-mail alerts from the searched database until 22nd June 2017 revealed two additional articles (33,34). An inquiry in the expert network of the authors yielded four more articles that met inclusion criteria (35)(36)(37)(38).…”
Section: Study Selectionmentioning
confidence: 99%
“…Lastly, there is a strong need for TBI pediatric interventions tailored to the developing brain so that our understanding of WM development (or lack thereof) and the development of other cognitive domains post-injury can be specifically targeted with empirically-based cognitive interventions. While still a young area of research, several studies have investigated the efficacy of certain interventions such as cognitive training programs, on cognitive performance in attention, memory, and daily functioning (Catroppa et al, 2015) as well as on specific aspects of WM (Phillips et al, 2016). The findings of these studies are encouraging, with positive effects of cognitive training found at 3 months (Phillips et al, 2016) and 6 months (Catroppa et al, 2015) post-injury.…”
Section: Discussionmentioning
confidence: 99%
“…While still a young area of research, several studies have investigated the efficacy of certain interventions such as cognitive training programs, on cognitive performance in attention, memory, and daily functioning (Catroppa et al, 2015) as well as on specific aspects of WM (Phillips et al, 2016). The findings of these studies are encouraging, with positive effects of cognitive training found at 3 months (Phillips et al, 2016) and 6 months (Catroppa et al, 2015) post-injury. However, additional research is needed to determine whether cognitive interventions have a positive impact on the long-term developmental trajectory of WM and other skills.…”
Section: Discussionmentioning
confidence: 99%
“…Both of these studies, however, lacked a comparative training program. In addition to AMAT-c, other pediatric programs for cognitive training have been published and tested, including computerized home-based tools; however, these have only been validated in children with specific ABI etiologies, such as cancer survivors [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%